2022
DOI: 10.3389/fmicb.2022.924398
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Mechanisms and Application of Lactic Acid Bacteria in Bakery Products: A Review

Abstract: Bakery products are nutritious, but they are susceptible to fungal contamination, which leads to a decline in quality and safety. Chemical preservatives are often used to extend the shelf-life of bakery products, but long-term consumption of these preservatives may increase the risk of chronic diseases. Consumers increasingly demand food with fewer chemical preservatives. The application of lactic acid bacteria (LAB) as a novel biological preservative not only prolongs the shelf-life of bakery products but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 122 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Following standard procedures for isolation and identification, a total of 30 strains of LAB were isolated from chicken intestine. The isolates were identified as Lactobacillus brevis ( L. brevis ) 14 , Lactobacillus plantarum ( L. plantarum ) 7 , Lactobacillus acidophilus ( L. acidophilus ) 5 , Pediococci spp. 2 , Lactobacillus casei ( L. casei ) 1 , and Lactobacillus fermentum ( L. fermentum ) 1 ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following standard procedures for isolation and identification, a total of 30 strains of LAB were isolated from chicken intestine. The isolates were identified as Lactobacillus brevis ( L. brevis ) 14 , Lactobacillus plantarum ( L. plantarum ) 7 , Lactobacillus acidophilus ( L. acidophilus ) 5 , Pediococci spp. 2 , Lactobacillus casei ( L. casei ) 1 , and Lactobacillus fermentum ( L. fermentum ) 1 ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…LAB can help maintain a healthy balance of microorganisms in the gut and contribute to digestion, nutri-ent absorption, and immune function [9][10][11][12] . Additionally, LAB have antimicrobial properties that can inhibit the growth of harmful bacteria, making them useful in food preservation and the prevention of foodborne illnesses 6,9,[13][14][15][16] . Their diverse metabolic capabilities and beneficial properties make them a significant group of bacteria in both scientific and industrial contexts 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have evaluated the antifungal activity of Reu in vitro at different concentrations, and the results have shown that the minimal inhibitory concentrations (MIC) ranged from 1.89 mM to 7.58 mM and from 4 to 10 mmol/L [ 38 , 39 ].…”
Section: Reuterinmentioning
confidence: 99%
“…Lactic acid bacteria are widely used not only in the food industry but also in animal production, including as feed additives or silage preparations [22], and in agriculture as safe and effective biological agents for combating bacterial and fungal phytopathogens. The mechanism of their action is the production of lactic and acetic acids, bacteriocins, reuterin and other antimicrobial compounds, as well as the removal of reactive oxygen species [33]. In recent years, scientists' interest has also concentrated on the search for microorganisms other than LAB, capable of inhibiting the growth of pathogenic microorganisms.…”
Section: Role Of Antagonistic Microorganisms In Ensuring Food Safetymentioning
confidence: 99%